Legislative performance and the electoral connection in European Parliament elections - Chiru, M (Wiley, 2023)
The absence of an electoral connection is a widely held assumption in the scholarship on the European Parliament (EP) and a cause of serious normative concern about the functioning of the European Union. Weak individual legislator accountability is part of this assumption, even if we still know little about the extent to which legislative performance matters for citizens in EP elections that allow preferential voting. This study is the first to analyse how legislative performance influences the preference vote shares of members of the European Parliament (MEPs) and whether this is moderated by their parties’ EU salience and incumbent intra-party competition. It draws on an original dataset that combines candidate and electoral data from three rounds of EP elections held between 2004 and 2014 under open or flexible list rules with information on individual legislative activity (i.e., number of reports, parliamentary questions and speeches) and leadership positions at EP and committee level. One dimension of legislative performance, report writing, is associated with a larger share of preference votes but only for incumbents of parties assigning high salience to the EU. While MEPs win a higher share of preference votes when they face limited co-partisan incumbent competition, this factor does not moderate the electoral connection.